PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 105 PEKANBARU - Iswari Utami; Hendri Marhadi; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning social study class IV SD Negeri 105 Pekanbaru. KKM achieved by school was 70. From 36 students who achieve KKM just 16 students (44.44%) while students who did’nt achieve KKM is 20 students (55.56%) with a class average of 70.66. The purpose of this research to improve learning outcomes IPS class I V SD Negeri 105 Pekanbaru with the application of learning models cooperative pair checks type. The results obtained by the average value of 70.66 basic score increased in the first cycle of 9.68% to 77.55. In the second cycle the average value of students also increased by 25.38% to 89.02. On the basic of classical completeness score IPS student learning outcomes is only 44.44% (not complete). After the professor of applied learning model cooperative pair checks type in the first cycle classical completeness increased to 75% (complete), and the second cycle of classical completeness obtained are increased to increase to 100%. Activities of teachers at the first meeting of first cycle acquire a percentage of 66.67% with good category. The second meeting increased to 75% in good category. In the first meeting of second cycle increased to 87.5% with very good category. At the second meeting increased to 91.67% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 58.33% with enough category. The second meeting increased to 75% in good category. In the first meeting of the second cycle increased to 79.17% with good category. At the second meeting increased to 87.5% with very good category.Keywords : Social Studies Learning Outcomes, Cooperative Learning Pair Checks Type